2011
DOI: 10.1007/s12035-011-8225-x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a Neuroprotective Agent in the Rodent Models of Parkinson’s Disease: Is it All Set to Irrefutable Clinical Translation?

Abstract: Parkinson's disease (PD), a neurodegenerative disorder, is characterized by the selective degeneration of the nigrostriatal dopaminergic neurons, continuing or permanent deficiency of dopamine, accretion of an abnormal form of alpha synuclein in the adjacent neurons, and dysregulation of ubiquitin proteasomal system, mitochondrial metabolism, permeability and integrity, and cellular apoptosis resulting in rigidity, bradykinesia, resting tremor, and postural instability. Melatonin, an indoleamine produced almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 124 publications
(216 reference statements)
0
23
0
Order By: Relevance
“…The results indicated that the generation of ROS was increased after MA exposure (Fig. 6C, p < Extensive investigations demonstrate that MA is neurotoxic both in vivo and in vitro [24,25]. Interestingly, Li is found to be neuroprotective both in vivo and in vitro M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 11 as well and even could be benefit in treating neurodegenerative diseases, such as Alzheimer's disease [26].…”
Section: Ly294002 Reduces the Protective Effects Of LImentioning
confidence: 86%
“…The results indicated that the generation of ROS was increased after MA exposure (Fig. 6C, p < Extensive investigations demonstrate that MA is neurotoxic both in vivo and in vitro [24,25]. Interestingly, Li is found to be neuroprotective both in vivo and in vitro M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 11 as well and even could be benefit in treating neurodegenerative diseases, such as Alzheimer's disease [26].…”
Section: Ly294002 Reduces the Protective Effects Of LImentioning
confidence: 86%
“…14,31 Melatonin, the main secretory product of the pineal gland, can easily cross the blood-brain barrier and has plentiful neuroprotective properties such as regulating circadian rhythms and providing anti-inflammatory and neuronal protection. [32][33][34] As a naturally occurring compound, melatonin has potential effects on inhibiting autophagy through a redox-mediated scavenge of free radicals and lipid peroxidation, 35 as well as its well-known antioxidant properties. 36 Emerging evidence suggests that melatonin can be used as a neuroprotective agent in the rodent models of PD 32,37,38 by ameliorating the dysfunction of mitochondria, [39][40][41][42] blocking CASP3 (caspase 3, apoptosis-related cysteine peptidase) activation and cellular apoptosis, 43 and protecting TH (tyrosine hydroxylase)-positive nerve terminals.…”
Section: Introductionmentioning
confidence: 99%
“…Indole compounds are involved in the regulation of sleep, mood; it coordinates the work of the biological clock controlling circadian rhythm, exhibits anticancer properties, and plays a neuroprotective role. Indole derivatives are also compounds with anti-inflammatory and analgesic properties (Wurst et al 2004;Keszthelyi et al 2009;Esposito & Cuzzocrea 2010;Singhal et al 2012). Biological activity of phenolic acids is related to their antioxidant activity that protects the vital structures such as chromosomal DNA, structural proteins, enzymes, and LDL and lipids of cellular membranes from oxidative damage (Yeh et al 2009).…”
Section: Introductionmentioning
confidence: 99%